2012
DOI: 10.1096/fj.11-203323
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2increases fibroblast gene‐specific and global DNA methylationviaincreased DNA methyltransferase expression

Abstract: Although alterations in DNA methylation patterns have been associated with specific diseases and environmental exposures, the mediators and signaling pathways that direct these changes remain understudied. The bioactive lipid mediator prostaglandin E(2) (PGE(2)) has been shown to exert a myriad of effects on cell survival, proliferation, and differentiation. Here, we report that PGE(2) also signals to increase global DNA methylation and DNA methylation machinery in fibroblasts. HumanMethylation27 BeadChip arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 50 publications
3
34
0
1
Order By: Relevance
“…Our data suggest that the inhibition of adhesion signaling by PGE 2 represents a critical mechanism for the reversal of myofibroblast differentiation. We do note, however, that treatment of myofibroblasts with a FAK inhibitor did not reverse a-SMA expression to the same degree as PGE 2 , suggesting that PGE 2 may employ other mechanisms (e.g., activation of PTEN/inhibition of Akt [18], activation of the wnt/b-catenin signaling pathways [36], and modification of genespecific DNA methylation patterns [33]) that are responsible for reversal of myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our data suggest that the inhibition of adhesion signaling by PGE 2 represents a critical mechanism for the reversal of myofibroblast differentiation. We do note, however, that treatment of myofibroblasts with a FAK inhibitor did not reverse a-SMA expression to the same degree as PGE 2 , suggesting that PGE 2 may employ other mechanisms (e.g., activation of PTEN/inhibition of Akt [18], activation of the wnt/b-catenin signaling pathways [36], and modification of genespecific DNA methylation patterns [33]) that are responsible for reversal of myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have implicated FAK (30) and Akt (27) signaling, as well as endoplasmic reticulum stress (31), in myofibroblast differentiation; in addition, an epigenetic signature distinct from that of fibroblasts has been observed in myofibroblasts (32). All of these mechanisms represent potential targets that might mediate phenotypic reversal by PGE 2 ; indeed, this prostanoid is known to inhibit FAK and Akt activation (6,28), and to increase global DNA methylation in fibroblasts (33). Here, we observed that levels of Tyr397-phosphorylated FAK in myofibroblasts decreased within 15 minutes of PGE 2 treatment, and that inhibition of FAK was capable of reversing the myofibroblast phenotype.…”
Section: Discussionmentioning
confidence: 96%
“…Such changes could be due, in part, to alterations in the epigenetic state of the cells. PGE 2 has been shown to affect DNA methylation patterns in the intestine and increase global DNA methylation via induction of DNMT3a in fibroblasts 38 . It will be interesting in future studies to explore potential roles for epigenetic modifiers and to examine DNA methylation patterns before, during and after treatment with dmPGE 2 .…”
Section: Directions For Future Studies With Dmpge2mentioning
confidence: 99%
“…COX-2 is a critical modulator of PGE2 which, among its diverse functions, can mediate epigenetic changes through regulating the transcription of DNA methyltransferases, DNMT1, DNTM3a, and DNTM3b [59, 60]. Thus, there is an intriguing possibility that COX-2-regulated PGE2 influences the expression of proximal genes.…”
Section: 0 Discussionmentioning
confidence: 99%